2018
DOI: 10.1155/2018/8568424
|View full text |Cite
|
Sign up to set email alerts
|

Heritability Analysis and Phenotypic Characterization of Spider Plant (Cleome gynandra L.) for Yield

Abstract: Knowledge on phenotypic diversity among existing spider plant accessions is a milestone in the improvement of spider plant, which is a highly nutritious indigenous vegetable in Kenya. A study involving agronomic and morphological characterization of 49 spider plant accessions assembled from East and South Africa was carried out at the University of Nairobi Field Station for two seasons in a randomized complete block design with three replications. Phenotypic data was collected on growth habit, flower, petiole,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…We observed highly significant variation among advanced lines for biomass productivity, growth traits, leaf traits and flowering time in Gynandropsis gynandra . Similar observations for morphological traits have also been reported for worldwide accessions [ 3 , 55 ], East and Southern African accessions and cultivars [ 4 ], and accessions from South Africa and Kenya [ 54 ], Ghana [ 50 ], and Burkina-Faso [ 51 ]. This significant variation represents a valuable resource for sustainable and successful breeding programs for the species.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We observed highly significant variation among advanced lines for biomass productivity, growth traits, leaf traits and flowering time in Gynandropsis gynandra . Similar observations for morphological traits have also been reported for worldwide accessions [ 3 , 55 ], East and Southern African accessions and cultivars [ 4 ], and accessions from South Africa and Kenya [ 54 ], Ghana [ 50 ], and Burkina-Faso [ 51 ]. This significant variation represents a valuable resource for sustainable and successful breeding programs for the species.…”
Section: Discussionsupporting
confidence: 81%
“…We therefore hypothesize that phenotypes can accurately predict genotypes, but this should be confirmed with multi-environmental trials. Similarly, high broad-sense heritability estimates were reported for stem diameter, plant height, number of primary branches, leaf biomass, leaf area, leaflet length and width, and days to 50% flowering in the species [ 54 , 89 ]. This suggests that high genetic advancement is achievable for biomass and related traits in the species.…”
Section: Discussionmentioning
confidence: 88%
“…In agreement with the result of this study, [48] reported that eight ai commercial melon varieties tested had PDC values higher than GDC in all tested characteristics. e PDC value greater than GDC indicates that the character is heavily affected by environmental factors rather than genetic factors, while the PDC value that is almost the same as the GDC value indicates that the appearance of the characteristics is not much affected by the environment [49][50][51] [52], so the selection can be made based on the appearance of these characteristics [53,54]. Table 6 shows that the three characteristics observed in the five stages of maturity have PDC values almost the same as GDC.…”
Section: Genetic Parameter Analysismentioning
confidence: 99%
“…Using F 2 populations, Sogbohossou (2019) observed high broad-sense heritability for some agronomic traits and essential vitamins in the species. Moreover, Kangai Munene et al (2018) and Kiebre et al (2017) reported high broad-sense heritability for leaf biomass, fruit traits, plant height, stem diameter, primary branches number, and days to 50% flowering in G. gynandra (Table 1). More importantly, the genetic variance was higher than the environmental variance (Kangai Munene et al, 2018;Kiebre et al, 2017).…”
Section: Quantitative Variations and Breeding Valuementioning
confidence: 99%
“…Moreover, Kangai Munene et al (2018) and Kiebre et al (2017) reported high broad-sense heritability for leaf biomass, fruit traits, plant height, stem diameter, primary branches number, and days to 50% flowering in G. gynandra (Table 1). More importantly, the genetic variance was higher than the environmental variance (Kangai Munene et al, 2018;Kiebre et al, 2017). On the other hand, narrow-sense heritability of leaf yield and related traits ranged from low to high and trait-specific (Akita, 2020;Salaou, 2020).…”
Section: Quantitative Variations and Breeding Valuementioning
confidence: 99%